Pedoman Strategis Mendapatkan Permodalan Bank pada Pelaku Usaha UMKM - Hala, Yusriadi; Sambo, Eva Marin; Wiyana, Anim; Daud, Dahniar; Anwar, Anwar (Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
The aim of this leadership activity is to provide knowledge and understanding to MSME players in the Badung Bali area about how to get support or loans from banks. A classic problem faced by small business owners is the difficulty of accessing credit. This work is carried out through data presentation and discussion. This capital acquisition strategy training was held on July 27 2023 involving small and medium entrepreneurs in the Badung area of Bali. Extension is carried out through data presentation and discussion. It is hoped that the results of this work can help actors understand and prepare for their needs and learn tips for getting loans from banks. It is hoped that this mentoring process can continue so that MSME actors can obtain the best results.